Cells: building blocks of life - Silverstein, Alvin; Silverstein, Virginia B.; Bakacs, George (Englewood Cliffs, N.J. Prentice-Hall, 1969)
Describes the composition and functions of different types of cells.
Keywords: Cells -- Juvenile literature; Cells